Statins associated diabetes: state of the problem in 2018 - Zh. D. Kobalava; P. V. Lazarev; S. V. Villevalde (Российский кардиологический журнал, 2018)
Statin therapy is highly effective and obligatory method of cardiovascular risk reduction in primary and secondary prevention. It is well tolerated by patients. However the risk of new diabetes cases onset, associated with statins, remains discussed actively. The review is focused on recent data on the prevalence of this adverse event, risk/benefit ratio, possible mechanisms and patients populations with the highest risk of development of statin related diabetes. Practitioners tactics analyzed in diabetes development when taking statins. The article goes with recent international guidelines data, as the consensus letters; also, a comparison provided with novel medications used in cardiovascular prevention.